Renewable Energy: Policy Issues and Economic Implications in Turkey - Boluk, Gulden (International Journal of Energy Economics and Policy, 2013)
Current energy policy of Turkey is to increase the renewable energy share in total energy and to maximize benefit from existing potential until next 15 years. It was planed that the share of renewable energy resources in electricity production would be at least 30% by 2023 and government ensured some incentives such as feed-in tariff, investment incentives etc. for renewable energy. Moreover Turkish Energy Regulatory Agency (EMRA) announced that biofuel blending would be mandatory starting from 2013 and 2014 for bioethanol (2%) and biodiesel (1%), respectively. This study examines the current situation and potential of renewable resources and evaluates the impacts of renewable energy policy both on the energy sector and whole national economy. Renewable energy targets can generate around 275-545 thousand direct jobs possibilities in energy sector and 7.9 thousand tones natural gas and 464 thousand cubic meters fossil fuel saving by 2023. Net trade impact of renewable energy targets will be aggravated due to mandatory biodiesel blending since Turkey has oilseed deficit. In Turkey, utilization of all type of resources will contribute to economy but most feasible and sustainable renewable energy is biomass. Between the other renewables, biomass would provide highest social well-being in the country. Keywords: Turkey; renewable energy policy; sustainable development JEL Classifications: Q16; Q20; Q42